Instability and indeterminacy in a simple search and matching model - Michael Krause; Thomas A. Lubik (Deutsche Bundesbank, 2010)
We demonstrate the possibility of indeterminacy and non-existence of equilibrium dynamics in a standard business cycle model with search and matching frictions in the labor market. Our results arise for empirically plausible parametrizations and do not rely upon a mechanism such as increasing returns.
Keywords: E24; E32; J64; 330; search and matching; indeterminacy; match elasticity; Konjunkturtheorie; Gleichgewichtsstabilität; Arbeitsmarktflexibilisierung; Arbeitsuche; Matching; Theorie